2021
DOI: 10.3389/fvets.2021.756123
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Safety and Protective Efficacy of a waaJ and spiC Double Deletion Korean Epidemic Strain of Salmonella enterica Serovar Gallinarum

Abstract: With an aim to develop a highly attenuated and strongly immunogenic distinguishable vaccine candidate, a waaJ (a gene involved in the synthesis of lipopolysaccharide) and spiC (a virulence gene) double deletion Korean epidemic strain of S. enterica ser. Gallinarum (SG005) was constructed. Our results showed that the growth and biochemical characteristics were not altered by this double deletion. The double deletion strain contained dual markers. One was a bacteriological marker (rough phenotype) and the other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…SpiC is an effector protein encoded by SPI-2, which is secreted by the Salmonella type III secretion system (T3SS) and injected into host cells (19,20). It has been demonstrated that deleting spiC gene significantly reduces the virulence of Salmonella in mouse and chicken models (21). The spiC gene deletion strain of Salmonella Pullorum constructed by genetic engineering has been evaluated as a candidate vaccine for S. Pullorum (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…SpiC is an effector protein encoded by SPI-2, which is secreted by the Salmonella type III secretion system (T3SS) and injected into host cells (19,20). It has been demonstrated that deleting spiC gene significantly reduces the virulence of Salmonella in mouse and chicken models (21). The spiC gene deletion strain of Salmonella Pullorum constructed by genetic engineering has been evaluated as a candidate vaccine for S. Pullorum (22,23).…”
Section: Introductionmentioning
confidence: 99%